Technical approaches to select high‐performance instant skin smoothing formulations: Correlation of in vitro and in vivo assessment methods. Issue 5 (15th March 2019) - Maidhof, Robert; Knapp, Elizabeth; Liebel, Frank; Fair, Michael; Rubinson, Emily H.
Abstract: Background: Contractile films that smooth the surface of skin upon drying are popular among consumers due to their "instant" effect and perceivable smoothing benefits. The objective of our study was to correlate an in vitro measurement of contractile force with in vivo smoothing performance, thereby enabling rapid screening of film‐forming technologies for impactful cosmetic results. Methods: We introduce and characterize an in vitro method to measure drying stress of film‐containing formulations. This method is used to measure the drying stresses of seven different cosmetic film formulations. We then evaluate these formulas in a blinded clinical study, measuring their effect on under‐eye and Crow's Feet area smoothing through bioinstrumentation (3D PRIMOS imaging) and blinded expert grading of images. Results: The in vitro drying stress measurement was found to be repeatable and sensitive enough to detect differences between formulations with typical amounts of film‐forming agents. Significant correlation was found between the in vitro drying stress measurements and under‐eye smoothing measured by 3D imaging ( R 2 = 0.71). Expert grading confirmed that film formulas deliver perceivable smoothing in the under‐eye and Crow's Feet regions 15 minutes after application. Conclusion: The in vitro method described here can be used to predict the efficacy of formulations that deliver smoothing benefits to consumers. For consumer use, the esthetic properties of a formula should be balanced with film performance, guided by this model which predicts skin smoothing efficacy.